2020
DOI: 10.1111/jfpp.15153
|View full text |Cite
|
Sign up to set email alerts
|

Packaging potential of Ipomoea batatas and κ‐carrageenan biobased composite edible film: Its rheological, physicomechanical, barrier and optical characterization

Abstract: The present study aimed at developing composite edible film from a blend of Ipomoea batatas, κ‐carrageenan, and glycerol. Three different treatments by varying glycerol concentrations (5%‐TS1, 10%‐TS2 & 15%‐TS3) in film‐forming solution were prepared and resultant films were evaluated for rheological, physicomechanical, barrier, and optical properties. All the treatments showed film‐forming ability with varying degrees of distinction. The steady rheology of film‐forming solution containing 10 and 15% glycerol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Similarly, Martiny et al [45] demonstrated a significant reduction by 54 percent in water vapor permeability of carrageenan films imbibed with olive leaves extract; in addition, the formed films were more flexible. In agreement with the previous study, a steady refinement was noticed in the mechanical properties and water vapor permeability of Ipomoea batatas and kappa-carrageenan blended films [46]. Similar results were also obtained by Sedayu et al [47] in the case of carrageenan and nanocellulose composite films.…”
Section: Carrageenansupporting
confidence: 91%
“…Similarly, Martiny et al [45] demonstrated a significant reduction by 54 percent in water vapor permeability of carrageenan films imbibed with olive leaves extract; in addition, the formed films were more flexible. In agreement with the previous study, a steady refinement was noticed in the mechanical properties and water vapor permeability of Ipomoea batatas and kappa-carrageenan blended films [46]. Similar results were also obtained by Sedayu et al [47] in the case of carrageenan and nanocellulose composite films.…”
Section: Carrageenansupporting
confidence: 91%
“…The transparent films should be used in some food products, and the actual color of the product cannot be observed due to the turbidity of the prepared film or coating. However, opaque films can be used in dairy products, pharmaceuticals, or light-sensitive products (Bharti et al, 2021).…”
Section: Color Analysismentioning
confidence: 99%
“…Synthetic-based packaging is generally derived from synthetic polymer materials such as petrochemicals that are not biodegradable so it can pollute the environment [1]. In additions, natural-based packaging generally uses natural biopolymers such as proteins, polysaccharides, fats, and the addition of several other materials such as plasticizers and surfactants [2]. To reduce the problem of environmental pollution due to synthetic packaging, it is necessary to develop pertaining to natural-based packaging [3].…”
Section: Introductionmentioning
confidence: 99%